Possible interference of human beta-herpesviruses-6 and -7 in gastrointestinal cancer development - Sultanova A.; Chistjakovs M.; Chapenko S.; Donina S.; Murovska M. (Experimental Oncology, 2013)
Aim: The high incidence of gastrointestinal cancer combined with high mortality from the disease if diagnosed at a late stage, signifies the need for better diagnostic, prognostic and predictive tools. Human beta-herpesviruses have been suggested as possible cofactors in the development of gastrointestinal cancer. Methods: Sixty five patients with gastrointestinal cancer before surgery and without any treatment were enrolled in this study and divided into two groups depending on lymphocytes’ count: I group (n = 35) — lymphocytes > 1400x10⁶ /L and II group (n = 30) — lymphocytes < 1400x10⁶ /L. Nested polymerase chain reaction was used to detect latent and active stage of persistent human herpesvirus-6 and -7 infection, laser flow cytometry with monoclonal antibodies — to determine immunological parameters. Results: Activation of herpesvirus-6 and -7 was more frequently observed in the patients’ group with lymphopenia (HHV-6 1/1 (100%), HHV-7 4/8 (50%) and HHV-6 + HHV-7 6/9 (66%); p < 0.05). Cellular immune parameters were analysed in immunocompromised II group’s patients dependently on beta-herpevirus infection. Although number of leukocytes was higher in patients with active HHV-6/-7 infection (p = 0.01), number of lymphocytes CD3⁺, CD4⁺, CD8⁺ and CD38⁺ in patients with active HHV-6/-7 infection tended to decrease (p < 0.0001, P = 0.0002, p = 0.0001 and p < 0.0001, respectively). However, number of CD19+ had tendency to increase (p = 0.03). Conclusion: Activation of herpesvirus-6 and -7 may lead to decrease of lymphocytes total count and develop immunosuppression in patients with gastrointestinal cancer. Key Words: beta-herpesvirus-6, beta-herpesvirus-7, gastrointestinal cancer.